Self-awareness of bilingualism in advanced students of english - Pinheiro, Aline de Lima (Universidade do Vale do Rio dos Sinos, 2018)
Bilingualism has often been described by lay people as the ability of speaking two languages perfectly (HARDING-ESCH; RILEY, 2003) and by scholars as the native-like mastery of two languages (BLOOMFIELD, 1933). Although bilingualism has been the subjects of studies in many areas (ROMAINE, 1995), little attention has been given to students’ perceptions, especially the ones from English language schools. The aim of this research paper is to investigate, through the usage of a questionnaire and a discussion about bilingualism, whether advanced students from a language course consider themselves bilinguals and if they are able to justify their answers. From the data gathered, it could be inferred that most subjects who were part of the present research were aware of their abilities in English and could perceive themselves as bilinguals. Also, they were familiar with concepts of bilingualism that go beyond lay people’s assumption of what it means to be a bilingual. Even though there were no comparisons to native speakers’ competence, subjects still prioritized the active skills, in this case speaking, when describing bilinguals and bilingualism.
Keywords: Bilinguismo; Curso de Iínguas; Percepções; Bilingualism; Language course; Perceptions